Reliability of a Smartphone Compared With an Inertial Sensor to Measure Shoulder Mobility: Cross-Sectional Study - Roldán-Jiménez, Cristina; Martín-Martín, Jaime; Cuesta-Vargas, Antonio (JMIR Publicatins, 2019)
This study aimed to validate the use of the Nexus 4 smartphone as a tool for measuring humerus mobility during shoulder motion compared to a dedicated InertiaCube3 sensor. A total of 43 subjects participated in the study, with 27 affected by shoulder pathologies and 16 asymptomatic. Shoulder flexion, abduction, and scapulation were measured using both the InertiaCube3 and the Nexus 4 smartphone simultaneously. The results showed that the smartphone reliably recorded velocity values and demonstrated excellent interclass reliability for the humerus abduction axis of motion in all three movements. The humerus abduction axis of motion also showed excellent reliability for flexion and scapulation movements. Therefore, the study concludes that the Nexus 4 smartphone is a reliable and valid tool for recording velocity produced at the shoulder, comparable to the dedicated InertiaCube3 sensor. This finding is significant as smartphones are more affordable and widely available compared to dedicated sensors, making them a feasible option for clinicians to assess shoulder mobility.
Keywords: Telefonía sin hilo; Kinematics; Mobile phone; Shoulder; Smartphone